Penerapan Asas Kebebasan Berkontrak Dalam Perjanjian Konstruksi - Ferdian Saputra, Muhammad (Recital Review, 2025)
This paper discusses the application of the principle of freedom of contract in construction agreements in Indonesia and emphasizes the potential for injustice. Although this principle allows parties to create and design contracts freely, there is often an imbalance of power, especially between contractors and project owners. Construction work contracts are regulated by the Civil Code (KUHPERDA) and Law No. 2 of 2017 concerning Construction Services, but there are still loopholes that allow clauses that benefit project owners. Imbalance of bargaining power, unbalanced contract provisions, and disproportionate risk sharing are the main issues discussed. In order to protect the rights of all parties involved in a construction agreement, this paper analyzes the problem normatively and emphasizes the importance of implementing a fairer principle of freedom of contract.